Do Consumers Have the Willingness to Try Microalgae as an Alternative Protein Source? - Kasana, Tiara Miladiyatul; Setiawan, Budi; Shinta, Agustina (Universitas Panji Sakti, 2025)
The increasing consumption needs of society have led to a rise in food demand, which continues to grow along with the population increase. Every year, the government implements various efforts to meet these growing consumption demands. Using alternative food sources can meet the public's dietary needs. One such alternative is microalgae, which is considered a promising food source. However, it is still relatively unfamiliar to the public, necessitating strategies to raise awareness about this ingredient. Several factors can influence customer attitudes, making them more open to trying new things, thereby positively affecting consumer willingness to try microalgae as an alternative food source. This study aims to investigate the influence of environmental concerns, health interests, food neophobia, and knowledge on consumer attitudes toward trying microalgae as a preferred alternative protein source. It also examines whether consumer attitudes influence willingness to try microalgae moderated by self-efficacy. The research employed a quantitative approach, with a sample size of 400 respondents determined using multistage sampling. Primary data were collected through a closed questionnaire. Data analysis was conducted using descriptive statistical analysis and SEM-PLS (Structural Equation Modeling-Partial Least Square) with the WarpPLS 8.0 software. The results indicate that environmental concern, health interest, and knowledge have positive and significant effects on consumer attitudes, while neophobia has a negative and insignificant effect. Furthermore, consumer attitudes influenced willingness to try, with self-efficacy strengthening the relationship between attitudes and willingness to try microalgae as a preferred alternative protein source.